Compensation as Capital in Improving Performance and Organizational Commitment - Ade Febrianto; Rupus Rupus (Yayasan Edukasi Cakrawala Nusantara, 2025)
This research discusses Compensation as Social Capital in Building a Productive Organization. The Compensation Policy has been listed in the Perpu in Lieu of Law of the Republic of Indonesia Number 2 of 2022 concerning Job Creation in Chapter IV of Manpower Part Two of Article 61A. The research used by the author uses a descriptive qualitative method with theoretical data collection techniques, in the sense of a method based on descriptions in the form of sentences that are orderly, coherent, logical and effective. The results of this study show that compensation has a significant effect as capital in improving employee performance and organizational commitment.